2023
DOI: 10.3390/buildings13041049
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Conceptual Design and Self Health Monitoring Program in a Vertical City: A Case of Burj Khalifa, U.A.E.

Abstract: Burj Khalifa, a notable landmark in a growing landscape of skyscrapers, along with other tall structures, has dramatically transformed the morphology of Dubai and elevated it to global prominence. This masterpiece was designed to attract international interest, as it diversifies the economy from an oil-based one towards one that is tourist-and servicebased. However, the foremost design input and major challenges of the super-tall building are associated with the increase in height, which put them at risk of wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…Ndagi [41] asserts that descriptive research involves collecting data to examine and explain current practices, existing conditions, attitudes, reasons, and ongoing processes. However, the primary goal of descriptive research is not solely to explain what exists but to provide clarity on the discovered information [42][43][44][45]. The review process entails reevaluating past studies related to the spatial transformation of Yangon City, with a specific focus on understanding the key enablers to the public spaces transformation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ndagi [41] asserts that descriptive research involves collecting data to examine and explain current practices, existing conditions, attitudes, reasons, and ongoing processes. However, the primary goal of descriptive research is not solely to explain what exists but to provide clarity on the discovered information [42][43][44][45]. The review process entails reevaluating past studies related to the spatial transformation of Yangon City, with a specific focus on understanding the key enablers to the public spaces transformation.…”
Section: Methodsmentioning
confidence: 99%
“…While previous studies [43,49,50] emphasized the insignificance of industrial emissions compared to automobile emissions in the urban atmosphere, Fan et al [17] identified a key source of atmospheric pollution in Yangon.…”
Section: Urban Growth Of Yangon and Its Land Usementioning
confidence: 99%
“…Inventive technologies have been used in the conservation of heritage buildings around the world with proven efficacy [18][19][20]. These methods include documentation, diagnostic, and treatment, where many of the techniques have proved to be non-destructive and productive.…”
Section: Contemporary Methodologies For the Conservation Of Architect...mentioning
confidence: 99%
“…Research projects are aimed at studying various features of design and construction. Such projects were launched to learn more about wind loads and vortex resonance [17,18], basic structural and construction systems [19], the involvement of information modeling technologies and advanced construction methods and techniques [20], as well as novel materials and products [21].…”
Section: Introduction 1features Of Implementation Of Sophisticated Co...mentioning
confidence: 99%